Didymoplexiella trichechus (J.J. Sm.) Garay and a new variety of Didymoplexis cornuta J.J. Sm. (Orchidaceae) in Borneo - Hirokazu, Tsukaya; Monica Suleiman; Hiroshi, Okada (Japanese Society for Plant Systematics, 2014)
We report the occurrence of Didymoplexiella trichechus (J.J. Sm.) Garay and Didymoplexis cornuta J.J. Sm. in Sabah, Borneo, Malaysia. They were considered to be endemic to Sumatra and Java, respectively, but were discovered during a botanical expedition in the Maliau Basin Conservation Area. We also determined the collection of Didymoplexis cornuta to represent a novel variety, D. cornuta var. maliauensis Tsukaya, M. Suleiman & H. Okada.